2018
DOI: 10.1002/14651858.cd011901.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Visual inspection and dermoscopy, alone or in combination, for diagnosing keratinocyte skin cancers in adults

Abstract: Background Early accurate detection of all skin cancer types is important to guide appropriate management, to reduce morbidity and to improve survival. Basal cell carcinoma (BCC) is almost always a localised skin cancer with potential to infiltrate and damage surrounding tissue, whereas a minority of cutaneous squamous cell carcinomas (cSCCs) and invasive melanomas are higher-risk skin cancers with the potential to metastasise and cause death. Dermoscopy has become an important tool to assist specialist clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 534 publications
3
49
0
1
Order By: Relevance
“…Dermoscopy improves and completes clinical examination by revealing morphologic structures scarcely visible or invisible on the standard naked-eye physical examination, enhancing the most basic of diagnostic functions in dermatology: the visual inspection 15 . Dermoscopy has a well demonstrated value in the diagnosis of skin tumours, especially melanoma, but also of many non-tumoral dermatosis, such as infections and infestations, hair or nail diseases and inflammatory skin conditions [15][16][17] . In addition, nail fold dermoscopy may be applied for the screening of suspected connective tissue diseases instead of classic capillaroscopy 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Dermoscopy improves and completes clinical examination by revealing morphologic structures scarcely visible or invisible on the standard naked-eye physical examination, enhancing the most basic of diagnostic functions in dermatology: the visual inspection 15 . Dermoscopy has a well demonstrated value in the diagnosis of skin tumours, especially melanoma, but also of many non-tumoral dermatosis, such as infections and infestations, hair or nail diseases and inflammatory skin conditions [15][16][17] . In addition, nail fold dermoscopy may be applied for the screening of suspected connective tissue diseases instead of classic capillaroscopy 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Dinnes ve ark.nın yaptığı sistematik bir derlemede, görsel inspeksiyon ve dermatoskopinin tek başlarına ve birlikte uygulandıklarında elde edilen doğruluk oranları karşılaştırılmış ve her iki yöntemin birlikte kullanılmasının keratinositik deri kanserlerinde tanı doğruluğunu artırdığı gösterilmiştir. 30 35 Klinik ve dermatoskopik özelliklerin yanı sıra laboratuvar parametreleri BHK/SHK ayrımında yol gösterici olabilir.…”
Section: Mddk Türüunclassified
“…Yıldız HAYRAN ve ark.Tur ki ye Kli nik le ri J Med Sci. 2020;40(1):[26][27][28][29][30][31][32][33][34][35][36] …”
mentioning
confidence: 99%
“…Dermoscopy is efficient in the early diagnosis of melanoma [1][2][3] and possibly efficient in diagnosing keratinocyte carcinomas. 4 We have previously reported novel applications of dermoscopy applied in primary care. [5][6][7] In line with investigators in secondary care, 8,9 we reported that dermoscopy enhances the diagnosis of vascular skin lesions, 10 infections 11 and infestations in primary care.…”
Section: Introductionmentioning
confidence: 99%